A prospective study of the frequency of severe pain and predictive factors in women undergoing first-trimester surgical abortion under local anaesthesia. (February 2018) - Duros, Solène; Joueidi, Yolaine; Nyangoh Timoh, Krystel; Boyer, Laurence; Lemeut, Paul; Tavenard, Aude; Laviolle, Bruno; Levêque, Jean; Lavoué, Vincent
Abstract: Objective: To determine the frequency of severe pain among women and to identify the associated predictive factors during first-trimester surgical abortion under local anaesthesia (LA). Study design: A prospective cohort study from November 2013 to January 2014 at the Department of Gynecology and Obstetrics, Rennes, France. The study population was composed of one hundred and ninety-four patients who underwent an elective first-trimester surgical abortion under LA. In an anonymized questionnaire, the participants were asked to self-record their perceived pain level 30 min after the completion of the procedure using a 10 cm visual analogue scale (VAS). The main outcome measure was the frequency of severe pain among women, defined as VAS ≥ 7. Secondary outcome measure was the risk factor(s) for severe pain. Results: Severe pain (i.e. VAS ≥ 7) was experienced by 46% (95% CI: 39%-53%) of the population. Multivariate analysis confirmed that >10 weeks of gestation (OR: 2.530 [95% CI: 1.1–5.81], p = .0287) and having 0 or 1 child (OR: 5.206 [95% CI: 1.87–14.49], p = .0016) were significant independent factors of severe pain. Conclusion: Nearly half of the women experienced severe pain. More than 10 weeks of gestation and parity were predictive factors of severe pain. These findings should be useful in counselling women undergoing surgical abortion under LA.